2006
DOI: 10.1007/s11046-006-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgG and IgM in Sera from Canines with Blastomycosis using Eight Blastomyces dermatitidis Yeast Phase Lysate Antigens

Abstract: The objective of this study was to compare the efficacy of eight Blastomyces dermatitidis yeast phase lysate antigens (T-58: dog, Tennessee; T-27: polar bear, Tennessee; ERC-2: dog, Wisconsin; B5894: human, Minnesota; SOIL: soil, Canada; B5896: human, Minnesota; 48089: human, Zaire; 48938: bat, India) in the detection of the immunoglobulins IgG and IgM in serum specimens from canines with blastomycosis. An indirect enzyme-linked immunosorbent assay (ELISA, peroxidase system) was used to analyze sera collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Sporothrix schenckii (Ssl7 - St. John's Institute of Dermatology, London, United Kingdom) yeasts were grown in Brain Heart Infusion (BHI) broth for 3 days at 37°C [31]. Blastomyces dermatitidis (NCPF 4076-National Collection of Pathogenic Fungi, Colindale, London, United Kingdom) yeasts were grown in BHI at 37°C for five days [32]. A. fumigatus (strain 3111 – Laboratório de Micologia, Instituto de Pesquisa Clínica Evandro Chagas, FIOCRUZ, Brazil) was grown in Sabouraud Broth at 37°C for 96 h (cellular extract) or 3 weeks (culture filtrate).…”
Section: Methodsmentioning
confidence: 99%
“…Sporothrix schenckii (Ssl7 - St. John's Institute of Dermatology, London, United Kingdom) yeasts were grown in Brain Heart Infusion (BHI) broth for 3 days at 37°C [31]. Blastomyces dermatitidis (NCPF 4076-National Collection of Pathogenic Fungi, Colindale, London, United Kingdom) yeasts were grown in BHI at 37°C for five days [32]. A. fumigatus (strain 3111 – Laboratório de Micologia, Instituto de Pesquisa Clínica Evandro Chagas, FIOCRUZ, Brazil) was grown in Sabouraud Broth at 37°C for 96 h (cellular extract) or 3 weeks (culture filtrate).…”
Section: Methodsmentioning
confidence: 99%
“…Lysates 48938, B5896 and T‐58 provided high specificity but low sensitivity (as a result of many false negatives). Other studies of lysates 48938 and B5896 have shown these lysates provide good detection levels for antibody to blastomycosis but varying results for T‐58 . On the other hand lysate ER‐598 provides high sensitivity but low specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast a one-day period of lysis of H. capsulatum yeast cells was sufficient to produce a reagent that detected both delayed dermal hypersensitivity as well as being useful for the detection of antibodies in the ELISA [19,20]. With regard to our work with B. dermatitidis yeast phase lysate antigens many of our comparative studies have been done with reagents following growth, harvesting and allowing the cells to lyse for a period of 7 days [10,11,13,15,23,24].…”
Section: Discussionmentioning
confidence: 99%